2016
DOI: 10.1039/c6ra00080k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of side-wall functionalisation of multi-walled carbon nanotubes on the thermo-mechanical properties of epoxy composites

Abstract: Sidewall functionalisation of multi-walled carbon nanotubes using liquid rubber results in enhancement in thermo-mechanical properties of epoxy composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…27,28 Furthermore, with the increase of the applied potential to 10 mV, the stability of redox behaviour did not change, due to the electrostatic attraction between the imidazole and the carbon matrix. 29 The electrochemical study showed excellent stability of the functionalized material in the studied acidic environments. 3.4.…”
Section: Electrochemical Stabilitymentioning
confidence: 81%
“…27,28 Furthermore, with the increase of the applied potential to 10 mV, the stability of redox behaviour did not change, due to the electrostatic attraction between the imidazole and the carbon matrix. 29 The electrochemical study showed excellent stability of the functionalized material in the studied acidic environments. 3.4.…”
Section: Electrochemical Stabilitymentioning
confidence: 81%
“…10. These mechanisms are usually observed in nanocomposites containing high aspect ratio fillers like carbon nanotube and graphene [42][43][44][45]. All these mechanisms contribute to an increase in the total fracture surface area resulting in greater energy absorption compared with the neat epoxy and TiO 2 / epoxy nanocomposite.…”
Section: Fracture Toughness Of Epoxy Compositementioning
confidence: 99%
“…The effect of surface modification of nanofillers coupled with the interface interaction in the polymer matrix is a much probed area in current research. [ 14–18 ] The need for the development of innovative techniques to control the surface chemistry of the resulting nanomaterials is therefore highly mandatory. [ 19–21 ] With the advent of technology, engineered fillers, especially hybrid fillers, have gained much attraction in modifying the properties of polymers.…”
Section: Introductionmentioning
confidence: 99%